2019
DOI: 10.1093/jac/dkz268
|View full text |Cite
|
Sign up to set email alerts
|

High colonization rate of a novel carbapenem-resistant Klebsiella lineage among migratory birds at Qinghai Lake, China

Abstract: Objectives The emergence of carbapenemase-positive Enterobacteriaceae poses a serious threat to public health worldwide. Here we conducted a molecular surveillance study on carbapenem-resistant Enterobacteriaceae (CRE) colonization among migratory birds at Qinghai Lake in China. Methods A total of 420 samples from migratory birds and their surrounding environment were collected at three sites along the Qinghai Lake bird islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Permission was obtained from the Entry-Exit Inspection and Quarantine Bureau of China. Individual fresh fecal samples were collected using a sterile swab and subsequently diluted in sterile physiological saline solution as described previously (7). The diluted fecal samples were plated on MacConkey agar supplemented with 1 mg/liter cefotaxime and 1 mg/liter meropenem and incubated for 18 h at 37°C.…”
Section: Observationmentioning
confidence: 99%
“…Permission was obtained from the Entry-Exit Inspection and Quarantine Bureau of China. Individual fresh fecal samples were collected using a sterile swab and subsequently diluted in sterile physiological saline solution as described previously (7). The diluted fecal samples were plated on MacConkey agar supplemented with 1 mg/liter cefotaxime and 1 mg/liter meropenem and incubated for 18 h at 37°C.…”
Section: Observationmentioning
confidence: 99%
“…It may however reflect a lack of studies, or the accumulation of case reports that do not accurately reflect the true epidemiology. Indeed, investigations on AMR in wild birds sometimes revealed unexpected reservoirs, such as recently where a high proportion of CP-resistant NDM-5-producing Klebsiella pneumoniae was observed in migratory birds in China ( Liao et al, 2019 ). With regard to colistin resistance, a limited number of studies reported the plasmid-mediated mcr-1 gene in wild birds ( Tarabai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, we also found isolates resistant to imipenem, an antibiotic restricted exclusively to hospital use. High levels of resistance to carbapenems by bacteria isolated from migratory birds have been described by other authors [27,28]. Imipenem resistance was low (6.9%) and found mainly in E. coli, Proteus and Providencia.…”
Section: Discussionmentioning
confidence: 52%